2016
DOI: 10.1016/j.bone.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of osteoporotic women remaining at risk for fracture despite adherence to oral bisphosphonates

Abstract: Abstract:Background: Adherence to oral bisphosphonates is often low, but even adherent patients may remain at elevated fracture risk. The goal of this study was to estimate the proportion of bisphosphonate-adherent women remaining at high risk of fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…Some drugs have been developed to either reduce bone resorption (eg, bisphosphonates 198 ) or promote bone formation (hormonal replacement, 199 calcium, and vitamin D supplements). Combination and sequential treatment using both bone formation stimulator and bone resorption inhibitors have been attempted.…”
Section: Remineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some drugs have been developed to either reduce bone resorption (eg, bisphosphonates 198 ) or promote bone formation (hormonal replacement, 199 calcium, and vitamin D supplements). Combination and sequential treatment using both bone formation stimulator and bone resorption inhibitors have been attempted.…”
Section: Remineralizationmentioning
confidence: 99%
“…199 Generally, serious side effects, however, have now been associated with the extensive use of these drugs. 198,200,201 This, however, is not the main focus of this review. Only the materials with remineralizing action will be covered in details.…”
Section: Remineralizationmentioning
confidence: 99%
“…We suggested that compliance or oral bisphosphonate bioavailability deteriorates with time, leading to greater bone turnover, potentially resulting in greater fracture risk, as Drieling and colleagues demonstrated. 1 Although the current paradigm, as well as Drieling and colleagues, 1 suggests putting people on prolonged bisphosphonate treatment on a drug holiday to reduce oversuppression of bone turnover, 3 our results, as well as other observations indicating a greater incidence of fractures early after initiation of a drug holiday, [4][5][6] suggest that a drug holiday could be risky for many people and that re-evaluation of individuals on a prolonged course of oral bisphosphonates should probably include, in addition to clinical and densitometric evaluation, an assessment of bone turnover, to exclude what could be classified as subclinical treatment failure. Individuals with high bone turnover could thus be considered for a parenteral antiresorptive drug.…”
mentioning
confidence: 47%
“…We suggested that compliance or oral bisphosphonate bioavailability deteriorates with time, leading to greater bone turnover, potentially resulting in greater fracture risk, as Drieling and colleagues demonstrated. 1 Although the current paradigm, as well as Drieling and colleagues, 1 suggests putting people on prolonged bisphosphonate treatment on a drug holiday to reduce oversuppression of bone turnover, 3 our results, as well as other observations indicating a greater incidence of fractures early after initiation of a drug holiday, [4][5][6] suggest that a drug holiday could be risky for many people and that re-evaluation of individuals on a prolonged course of oral bisphosphonates should probably include, in addition to clinical and densitometric evaluation, an assessment of bone turnover, to exclude what could be classified as subclinical treatment failure. Individuals with high bone turnover could thus be considered for a parenteral antiresorptive drug.…”
mentioning
confidence: 50%